La enseñanza universitaria en la carrera de arquitectura de la tecnología de construcción con tierra cruda - una experiencia chilena - Pereira Gigogne, Hugo (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2003)
The present paper contains de experience of teaching earth building architecture and construction for students of schools of architecture at the city of Santiago of Chile since 1993 . The character of the course , objectives , pedagogical methods and contains are the result of the cooperation of traditional architecture , practical and field teaching building construction prototypes and parts of buildings by the students themselves . Very important to the positive result of these courses has been the information that came from CYTED program , specifically net HABITERRA since 1990 until year 2000 and now PROTERRA project from the same program .